Subordinate unless-clauses : Croatian and Slovenian in comparison to English - Ilc, Gašper (Array, 2019)
The complex subordinator unless (Cr. osim ako; Sl. razen če) introduces subordinate conditional clauses carrying exceptive meaning. It is usually assumed that unless-clauses are akin to (and replaceable by) negative if-conditional clauses, with the choice of one over the other being governed by semantic and pragmatic factors. This paper investigates subordinate unless-clauses in Croatian and Slovenian in comparison to English, primarily with regard to their interpretation, the possibility of expressing hypothetical and factual meanings, and the (non-)occurrence of pleonastic negation. Based on the data collected from referential corpora of Croatian, Slovenian and English we aim to establish not only the similarities that exist regarding unless-clauses across the three languages, but also some significant differences: as opposed to Croatian and Slovenian, English unless-clauses rarely/ /untypically express hypothetical meanings. As for the occurrence of pleonastic negation in unless-clauses, it never appears in English while in Croatian and Slovenian it is common but completely optional, with Slovenian displaying both properties of pleonastic negation – the assignment of the genitive of negation and no licensing of strong NPIs – and Croatian only one (no strong NPI licensing). Even though unless-clauses in both Slavic languages display very similar properties, their distribution with regard to negation is to some extent different: affirmative unless-clauses are more frequent in Slovenian than in Croatian, while the number of those with overt pleonastic negation is significantly smaller. We conclude that unless-clauses are an example par excellence of the fine-grained interplay of syntax, semantics and pragmatics, which primarily mediates the speaker’s communicative needs and intentions.